2023
DOI: 10.1139/cjz-2022-0131
|View full text |Cite
|
Sign up to set email alerts
|

Personality differences between sexes are present in a peaceful lizard, but not in an aggressive one: a chemical communication trial in two Liolaemus species

Abstract: Animal personality can be defined as behavioral individual consistency across contexts and time, and sociability may facilitate it. Boldness and exploration can be considered as social conflictive behaviors and in lizards, social scent can either diminish or promote social conflicts. We studied boldness and exploration in Liolaemus albiceps Lobo and Laurent, 1995 and L. coeruleus Cei and Ortiz, 1983, and tested whether L. albiceps, a fewer aggressive species, presents higher individual consistency in a sociall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…In crickets, individuals display higher aggressiveness and repeatability in the presence of conspecifics than in solitary conditions (Jäger et al, 2019). However, aggressiveness does not always promote individual consistency; Ruiz-Monachesi et al (2023) showed that a more peaceful species, Liolaemus albiceps, exhibited behavioural consistency, whereas a more aggressive species, L. coeruleus, did not.…”
Section: Influence Of Phylogeny On the Repeatability Of Behaviourmentioning
confidence: 99%
“…In crickets, individuals display higher aggressiveness and repeatability in the presence of conspecifics than in solitary conditions (Jäger et al, 2019). However, aggressiveness does not always promote individual consistency; Ruiz-Monachesi et al (2023) showed that a more peaceful species, Liolaemus albiceps, exhibited behavioural consistency, whereas a more aggressive species, L. coeruleus, did not.…”
Section: Influence Of Phylogeny On the Repeatability Of Behaviourmentioning
confidence: 99%